2000
DOI: 10.1111/j.1348-0421.2000.tb02565.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Serine Protease of Aeromonas sobria Is Controlled by the Protein Encoded by the Gene Lying Adjacent to the 3′ End of the Protease Gene

Abstract: We cloned a protease gene of Aeromonas sobria and determined its nucleotide sequence. The protease is composed of 624 amino acid residues and its calculated molecular weight is 66,737.7. The amino acid sequence showed the characteristic features of a bacterial serine protease. We expressed the protease gene in Vibrio parahaemolyticus from which the synthesized protease is secreted into the culture medium as the mature form, and purified the mature protease by successive column chromatographies.The size of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 39 publications
1
56
0
Order By: Relevance
“…Analysis of Nicked ASP Using Mass Spectrometry-In earlier studies, we purified ASP through a series of successive column chromatography steps using a DEAE-Sephadex A-25 column, a hydroxyapatite column, and a gel filtration column in an HPLC system (12). Because that method was both laborious and time-consuming, we have developed an improved method that entailed expressing recombinant ASP in A. sobria T94, a strain we found to produce large amounts of ASP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of Nicked ASP Using Mass Spectrometry-In earlier studies, we purified ASP through a series of successive column chromatography steps using a DEAE-Sephadex A-25 column, a hydroxyapatite column, and a gel filtration column in an HPLC system (12). Because that method was both laborious and time-consuming, we have developed an improved method that entailed expressing recombinant ASP in A. sobria T94, a strain we found to produce large amounts of ASP.…”
Section: Resultsmentioning
confidence: 99%
“…Purification of Nicked ASP-To purify ASP, A. sobria strain T94 harboring pSA19 -5528 was cultured in Luria broth supplemented with chloramphenicol (50 g/ml) for 20 h at 37°C with shaking (12). After cultivation, the cells were removed from the culture fluid by centrifugation, and ammonium sulfate was added to the supernatant to 50% saturation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already shown that ASP matures through a peculiar maturation pathway (24), illustrated in Fig. 9A.…”
mentioning
confidence: 99%
“…9A. Briefly, two proteins are encoded in the operon of the asp gene, ASP and ORF2 protein, which are located at the 5' and 3' ends of the operon, respectively (24). Both ASP and ORF2 protein move into the periplasmic space and associate in the space.…”
mentioning
confidence: 99%